Failure to detect equid herpesvirus types 1 and 4 DNA in placentae and healthy new-born Thoroughbred foals - Lara J. Brown (Journal of the South African Veterinary Association, 2019)
Equid herpesvirus type 1 is primarily a respiratory tract virus associated with poor athletic performance that can also cause late gestation abortion, neonatal foal death and encephalomyelopathy. Horizontal transmission is well described, whereas evidence of vertical transmission of equid herpesvirus type 1 associated with the birth of a healthy foal has not been demonstrated. This study sampled a population of Thoroughbred mares (n = 71), and their healthy neonatal foals and foetal membranes, to test for the presence of both equid herpesvirus types 1 and 4 using a quantitative polymerase chain reaction assay. Foetal membrane swabs and tissue samples were taken immediately post-partum, and venous blood samples and nasal swabs were obtained from both mare and foal 8 h after birth. Neither equid herpesvirus type 1 nor equid herpesvirus type 4 nucleic acid was detected in any sample, and it was concluded that there was no active shedding of equid herpesvirus types 1 and 4 at the time of sampling. Consequently, no evidence of vertical transmission of these viruses could be found on this stud farm during the sampling period.